Mechanism and Kinetics of Oligosilsesquioxane Growth in the In Situ Water Production Sol–Gel Route: Dependence on Water Availability. Issue 13 (4th February 2016) - Borovin, Evgeny; Callone, Emanuela; Ribot, Francois; Diré, Sandra
Abstract: Thiol‐functionalized nanobuilding blocks (NBBs) were synthesized from 3‐mercaptopropyltrimethoxysilane by using the in situ water production (ISWP) process in which the water needed to hydrolyze the precursor was provided by means of an esterification reaction. In the present study the reaction between 1‐propanol and chloroacetic acid was used. Whereas the growth of the Si oligomers was followed at room temperature and 100 °C using 1D 29 Si and 2D 1 H– 29 Si heteronuclear single quantum correlation (HSQC) NMR spectroscopic experiments, the amount of water delivered along the process was followed by means of 1 H NMR spectroscopy. The results show a good correlation between the evolution of the degree of condensation and the amount of water produced in situ. They also point to the preferential formation of cagelike structures and the narrowing of the species distribution over long reaction times. The average size of the growing oligomers was estimated from their diffusion coefficient, which was measured by means of 1 H diffusion‐ordered NMR spectroscopy (DOSY NMR). Like gel permeation chromatography, DOSY NNR showed a plateau between 70 to 100 hours in the growth of the oligomers, a time at which, according to 29 Si NMR spectroscopy, the well‐defined octakis(3‐mercaptopropylsilsesquioxane) is the major species. Abstract : Small thiol‐functionalized oligosilsesquioxanes were prepared by the in situ water production (ISWP) process in which water was homogenously generated by an esterification reaction. Manipulation of the temperature allowed the water production kinetics to be controlled, which played a major role on the degree of condensation (DOC) of the formed nanobuilding blocks.